Five little monkeys sitting in a tree - Christelow, Eileen (New York : Clarion Books, 1991)
Five little monkeys sitting in a tree discover, one by one, that it is unwise to tease Mr. Crocodile.
Keywords: Monkeys -- Fiction; Crocodiles -- Fiction; Counting; Stories in rhyme